Electrospun self-emulsifying core-shell nanofibers for effective delivery of paclitaxel - Ge, Ruiliang; Ji, Yuexin; Ding, Yanfei; Huang, Chang; He, Hua; Yu, Deng-Guang (Frontiers in Bioengineering and Biotechnology, 2023)
The poor solubility of numerous drugs pose a long-existing challenge to the researchers in the fields of pharmaceutics, bioengineering and biotechnology. Many “top-down” and “bottom-up” nano fabrication methods have been exploited to provide solutions for this issue. In this study, a combination strategy of top-down process (electrospinning) and bottom-up (self-emulsifying) was demonstrated to be useful for enhancing the dissolution of a typical poorly water-soluble anticancer model drug (paclitaxel, PTX). With polyvinylpyrrolidone (PVP K90) as the filament-forming matrix and drug carrier, polyoxyethylene castor oil (PCO) as emulsifier, and triglyceride (TG) as oil phase, Both a single-fluid blending process and a coaxial process were utilized to prepare medicated nanofibers. Scanning electron microscope and transmission electron microscope (TEM) results clearly demonstrated the morphology and inner structures of the nanofibers. The lipid nanoparticles of emulsions after self-emulsification were also assessed through TEM.The encapsulation efficiency (EE) and in vitro dissolution tests demonstrated that the cores-shell nanofibers could provide a better self-emulsifying process int terms of a higher EE and a better drug sustained release profile. Meanwhile, an increase of sheath fluid rate could benefit an even better results, suggesting a clear process-property-performance relationship. The protocols reported here pave anew way for effective oral delivery of poorly water-soluble drug.